Kay, William K.; Anne E. Dyer (eds.): European Pentecostalism - Usarski, Frank (REVER: Revista de Estudos da Religião, 2014)
Resenha: Kay, William K.; Anne E. Dyer (eds.): European Pentecostalism. Leiden/Boston: Brill 2011, ISBN: 978-90-04-20730-1, 416 p.